Exploring the relationship and integration of 21st-century skills in biology learning - Yudhistian Yudhistian; Imas Cintamulya (Biosfer: Jurnal Pendidikan Biologi, 2026)
The relationship and integration of 4C competences, biological literacy, creative problem-solving, and science process skills in biology learning are rarely analyzed simultaneously. On the other hand, integrating the four skills is important in 21st-century biology learning. The research aim is to explore the relationship and integration of 21st-century skills in biology learning, including 4C competence, biological literacy, creative problem-solving, and science process skills. The research method was quantitative research with a non-experimental explanatory design using 44 participants through filling out questionnaires, which were then analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) at the 5% significance level. The results prove that 4C competences have a significant influence on biological literacy; 4C competences have a significant influence on creative problem-solving; 4C competences have a significant influence on science process skills; biological literacy has a significant influence on creative problem-solving; biological literacy has a significant influence on science process skills; and creative process skills have a significant influence on science process skills. The research concluded that 4C competences through biological literacy and creative problem-solving skills significantly affect science process skills. The study has direct practical implications for educators in developing innovative biology learning strategies that integrate 21st-century skills through strengthening 4C competencies. This integration is crucial not only for improving biology literacy, creative problem solving, and scientific process skills but also as an essential step in enhancing the quality of future biology teachers.